PENINGKATAN ANGIOGENESIS PADA PROSES PENYEMBUHAN LUKA PASCA PENCABUTAN GIGI MARMUT (Cavia cobaya) SETELAH PEMBERIAN GEL EKSTRAK TERIPANG (Stichopus noctivagus) 75% - , CORNITA AYU SULISTIANI; , drg. Tunjung Nugraheni, M.Kes. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Sea cucumber (Stichopus noctivagus) traditionally has been used for treating wound. It contains saponin, flavonoid, chondroitin sulfate and glycosaminoglycans which play a role in wound healing process. Angiogenesis or growth of new blood vessel is an important stage in wound healing. Blood vessel is required to provide nutrients and oxygen for tissue after injury. The aim of this study was to observe the effect of 75% sea cucumber gel on the angiogenesis of wound healing process after tooth extraction of the guinea pig (Cavia cobaya). Sea cucumber was extracted into gel with concentration of 75%. Subjects (16 guinea pigs) was divided into 2 groups (treatment and control groups). Tooth extraction was performed on the lower central incisive. Seventy five percents sea cucumber gel was applied into the wounded socket of the treatment group and CMC 2% was applied into the wounded socket of the control group. Guinea pigs were sacrificed at 1, 3, 7 and 14 days after tooth extraction. The mandibles were processed for histological examination prior to hematoxylin eosin staining. Blood vessels were observed under microscope. The data were analyzed statistically with one way ANOVA and LSD. ANOVA showed significant difference among groups (p<0,05), indicating that sea cucumber stimulated angiogenesis. The number of blood vessels showed significant difference at 3, 7 and 14 days after tooth extraction (p<0,05) compared to the control group. It was concluded that the application of 75% sea cucumber gel increases angiogenesis in socket of wound healing process after tooth extraction of guinea pig. Key words: Sea cucumber (Stichopus noctivagus), angiogenesis, wound healing.